The value of tourism public opinion management in social governance: A study on the impact of electronic word-of-mouth perception on people’s livelihood well-being - Li, Xiuxiang; Wu, Yingqi; Jiang, Yi (Frontiers in Psychology, 2022)
In the process of tourism market upgrading and tourist iteration, tourism enterprises will face a more complex public opinion environment. It has become the focus of the tourism industry that they need to find a way to design a socialized approach to managing tourism public opinion and concentrate on the social governance, so as to enhance people's welfare. The role and influence of public opinion word-of-mouth has been extensively studied in the literature from the perspective of tourist or consumer behavior, but the in-depth exploration of the moderating mechanisms of individual tourist characteristics and environmental element is urgently needed. Therefore, combined with the background of the Internet era, we use SPSS and SmartPLS software for data analysis, in order to explore the happiness performance of tourists in contact with electronic word-of-mouth, and focus on the moderating effect of individual characteristics and environmental factors. The results show that visitors' perception of electronic word-of-mouth has a significant positive impact on their well-being experience, while individual characteristics and environmental factors show significant moderating effects. Thus, the study explores the value of tourism public opinion management in social governance centered on tourists' electronic word-of-mouth perception, which can help tourism enterprises effectively prevent and resolve the risks affecting social harmony and stability in the field of culture and tourism, and create a safe and stable cultural and tourism market environment.